A new species of Sparsorythus Sroka & Soldán, 2008 (Ephemeroptera: Tricorythidae) from Tamil Nadu, India - Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2021)
Sparsorythus srokai sp. nov. is described from the Veerapandi River, Theni district, Tamil Nadu, India based on nymphs of both sexes. The nymphs of Sparsorythus srokai sp. nov. can be distinguished by the following combination of characters: i) presence of lateral setae in each segment of caudal filaments, ii) dorsal surface of labrum entirely covered with scattered ribbon-like bristles, iii) posterior margin of mesonotum reaching abdominal segment III in both sexes, and iv) left prostheca with several pointed teeth apically. The new species is compared with other Indian species: S. gracilis Sroka & Soldán, 2008, S. sivaramakrishnani Sivaruban, Srinivasan, Barathy, Rosi & Isack, 2021 and S. nanjangudensis Muthukatturaja & Balasubramanian, 2021. The distributional map and key to the genus Sparsorythus in Southern India are also given.